2008
DOI: 10.1111/j.1475-3588.2007.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Five Years On: Public Sector Service Use Related to Mental Health in Young People with ADHD or Hyperkinetic Disorder Five Years After Diagnosis

Abstract: Background: Little is known about ongoing service use among young people with ADHD, but this information is important to the development of services to support these young people. Methods: A cohort of young people with ADHD or hyperkinetic disorder (n ¼ 115) was followed up five to seven years after diagnosis. Details are presented of their use of public sector services over the 12 months preceding reassessment, compared to young people with ADHD from a large epidemiological study. Results: Most children remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…It would therefore appear that the persistence rates of childhood ADHD into adolescence reported in this study are comparable to those reported in other countries. 5,6 The higher prevalence of primarily inattentive symptoms is in keeping with trends in other studies, as is the general assumption that while hyperactive and impulsive behaviour becomes less prominent as individuals with ADHD age, symptoms of inattention remain prevalent. 6,7 This particular sample of adolescents reported a significant number of psychiatric and adjustment difficulties.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It would therefore appear that the persistence rates of childhood ADHD into adolescence reported in this study are comparable to those reported in other countries. 5,6 The higher prevalence of primarily inattentive symptoms is in keeping with trends in other studies, as is the general assumption that while hyperactive and impulsive behaviour becomes less prominent as individuals with ADHD age, symptoms of inattention remain prevalent. 6,7 This particular sample of adolescents reported a significant number of psychiatric and adjustment difficulties.…”
Section: Discussionsupporting
confidence: 84%
“…4 With this in mind, a recent study of 157 individuals who had been diagnosed with ADHD between the ages of 6 and 15 years found that on the basis of parents' reports, 60% of these individuals still met the DSM-IV criteria for ADHD 5 years after diagnosis. 5 There would therefore appear to be convincing evidence of noteworthy persistence rates into adolescence for both full DSM-IV criteria and partial-remission ADHD.…”
Section: Prevalence Of Attention-deficit/ Hyperactivity Disorder (Adhmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the prevalence of disorder provides little detail about the individual needs of these children, which will be influenced by their family and social circumstances in addition to the presence/absence of psychopathology. However, clinical samples provide very misleading information about the prevalence of childhood psychiatric disorder and its correlates, because only a small and atypical group of children access services (Ford, Fowler, Langley, Whittinger, & Thapar, 2007b). While we should not assume that the presence of impairing psychopathology identifies all need, these estimates provide a firmer foundation for service planning than historical levels of provision or short‐term policy priorities (Flisher et al, 1997; Jenkins, 2001).…”
Section: How Many Children Might Need Services?mentioning
confidence: 99%
“…However, as a result of an often complex assessment and treatment process, inefficient methods of data collection, and difficulties tracking and monitoring long-term treatment, little is known regarding the long-term outcomes of those receiving recommended service intervention(s) 31,33,34…”
Section: Introductionmentioning
confidence: 99%